(untitled) (Colombia Medica, 1988)
We’ve come across the first case of tumor calcinosis, described in the Colombian and Latin American literature, and the current literature has been reviewed. We’re dealing with a tumor-like entity that calcifies soft tissues and whose cause is likely to be a congenital abnormality in the phosphaturic effect of the parathormone. Biochemically, it is characterized by normal calcium levels and a tendency to high phosphorus levels. It has a characteristic radiological and histological picture. The etiological treatment would be based on phosphorus-binding antacids such as aluminum hydroxide. Surgery plays a palliative role by dying up incapacitating and painful masses. Its frequency is very low. Only 150 cases have been described in the literature.